Winter's coming : a story of seasonal change - Thornhill, Jan (Owl Kids, 2014)
When Lily, a young snowshoe hare, hears that winter is coming, she does not know what to expect, even as the other animals explain what they do to cope with the change of seasons, although, they note, snowshoe hares do not need to do the same.